Under the Western eyes: Representation of cultural difference in 19th century French travel writing on the Dutch East indies - Mustofa, Andi; Novitasari, Hilda Dian Nova; Artanti, Yeni (NOTION: Journal of Linguistics, Literature, and Culture, 2025)
The 19th century as the peak period of colonization and the golden period of Western travel writing creates a complex context in intercultural interactions and representations of foreign cultures. The travel writing highlights the interactions of Western explorers with cultural diversity and the dynamics of power in intercultural relations. The research aims to analyze the representation of cultural difference and intercultural power relations reflected in 19th century French travel writings. The travel writings used are Voyages autour du monde et naufrages célèbres by Gabriel Lafond de Lurcy (1843) and Un Séjour dans l'île de Java (1898) by Jules Leclercq.  Grounded in Said’s theory of Orientalism, the research shows that representations of cultural difference were shaped by narratives of othering and ethnocentrism, and that intercultural encounters reflected unequal power relations that sustained Western dominance. In this context, 19th century French travel writings reinforced the discourse of orientalism and ethnocentrism, with representations of the East serving as a tool to sustain Western dominance and superiority. This study contributes to the understanding of how 19th century European literary narratives participated in cultural hegemony.